2001
DOI: 10.1017/s1074070800021003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spatial Break-even Variability in Fields with Two or More Management Zones

Abstract: Farmers are interested in knowing whether applying inputs at variable rates across a field is economically viable. The answer depends on the crop, the input. their prices, the cost of variable rate technology (VRT) versus uniform rate technology (URT). and the spatial and yield response variability within each tield. Methods were investigated for determining the range of spatial variability over which the rctum t o VRT covers its additional cost compared with URT in fields with rnultiple management zones. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Cotton is a high-value, high-input crop requiring large applications of P and K in general. English et al (2001) suggested that VR applications of fertilizer could lead to increased yields and/or lower levels of fertilizer use compared to uniform-rate applications.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is a high-value, high-input crop requiring large applications of P and K in general. English et al (2001) suggested that VR applications of fertilizer could lead to increased yields and/or lower levels of fertilizer use compared to uniform-rate applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of spatial yield monitor information, it is possible that farmer overconfidence (i.e., underestimating within-field yield variability) could influence the decision to adopt variable rate application technologies. Without yield monitor information, the farmer would perceive more spatially homogenous yields and be less likely to use variable rate input application techniques (English, Mahajanashetti, and Roberts, 2001;Larson and Roberts, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this particular farmer may decide not to invest in VR technology to apply inputs at variable rates across different sections of the field. As English, Mahajanashetti, and Roberts (2001) have shown, the economic viability of VR input application depends critically on the degree of the spatial variability of the farmer's fields; higher spatial variability results in higher returns from the use of VR application technologies. However, if the farmer's prior perception of spatial yield variability is lower than the true spatial yield variability, an error could be made in the grower's decision-making about whether or not to adopt VR technology.…”
Section: )mentioning
confidence: 99%
“…Roberts et al (2000) developed a general framework to evaluate the returns of variable rate nitrogen application. English et al (2001) extended the framework for use in a field with multiple management zones. They concluded that the final decision of whether to use variable rate (site-specific) over uniform rate varies from field to field, depending on the spatial variability of the soil and the yield response variability among the management zones.…”
Section: Economic Advantages Of Site-specific Irrigationmentioning
confidence: 99%